Explore BrainMass

# Solve Equation

Not what you're looking for? Search our solutions OR ask your own Custom question.

This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

Please see attachment for equation to be solved.

https://brainmass.com/math/basic-algebra/solve-equation-functions-21879

## SOLUTION This solution is FREE courtesy of BrainMass!

Given,

Y'''' - 2 Y ''' + 2 Y'' - 2Y' + Y = 0 ---(1)

Theorems to be used.
a) y' ---> d/dx (y)
b) d/dx (Y^n) = n Y ^ (n-1)
c) Integration of (Y') = Y
d) Integration of (Y^n) = (Y^n+1)/n+1
e) Integration of (Constant) = Y

Integrating (1) by using the above theorems

Y''' - 2 Y '' + 2 Y' - 2Y + (y^2)/2 = 0 ---(2)

Integrating (2) by using the above theorems

Y'' - 2 Y ' + 2 Y - Y^2 + (y^3)/6 = 0 ---(3)
Integrating (3) by using the above theorems

Y' - 2 Y + Y^2 - Y^3/6 + (Y^4)/24 = 0 ---(4)

Integrating (4) by using the above theorems

Y - Y^2 + Y^3/3 - Y^4/24 + (y^5)/120 = 0 ---(5)

Solving the above equation,

Y^5 - 5Y^4 + 40 Y^3 - 120Y^2 + 120 Y = 0